الضغوطات النفسية لدى عينة من الممرضات العاملات بنظام المناوبة الليلية في المؤسسة الاستشفائية المتخصصة الأم و الطفل الحكيم سعدان الأغواط - حرزلي مارية; بن يحي مداني (My University, 2018)
The present study aims to know (psychological stress in a sample of nurses working in the night shift system in the specialized hospital institution for mother and child wise Saadane Laghouat) *To achieve this study, the sample was selected in a deliberate manner consisting of 50 nurses for public health. To achieve the purpose of the study, the descriptive approach was followed for being the most suitable for this study and the collection of information. The methodology of the field research was based on the following tools: The questionnaire, which consisted of 30 items, was conducted in the field and was applied in the field and was based on the following statistical methods: Test T, repetitions and percentages. The following results: 1/- The level of pressure in a sample of nurses working night shift system in the specialized hospital for mother and child wise Saadane high. 2/- There were no statistically significant differences in the psychological stress in a sample of nurses working in the night shift system in the specialized hospital for mother and child Hakim Saadane attributed to the variable age. 3/- There are no statistically significant differences in the psychological stress in a sample of nurses working in the night shift system in the specialized hospital for mother and child Hakim Saadane attributed to the variable social situation. 4/- There are no statistically significant differences in the psychological stress in a sample of nurses working in the night shift system in the specialized hospital institution for mother and child Hakim Hakim Saadane attributed to the variable of seniority in the work